(untitled) (Fiep Bulletin - online, 2016)
This research presents a case study in a state school in southern Brazil, whose objective was to perform an ergonomic analysis in teachers of a high school. Through the questionnaire and analysis of the activity, it was found that most complaints regarding the pain was related to cervical region (neck and cervical spine) and upper body (shoulders, arms and hands) followed by lumbar spine. Teacher activity provides the appearance of these complaints due to repetitive work, power applications, trunk twisting motions and fast-paced work. The study concluded that the teaching activity, by its operational, organizational characteristics, contributes significantly to the development of musculoskeletal disorders and occupational health in these professionals.